Broer-Kaup System with Corrections via Inverse Scattering Transform - Xueru Wang; Junyi Zhu (Advances in Mathematical Physics)
The Broer-Kaup system with corrections is considered. Based on the inverse scattering transform, we extend the perturbation theory to discuss the adiabatic approximate solution and ε-order approximate solution of one soliton to the Broer-Kaup system with corrections.